Serenity bench / Saifullah Ammar ... [et al.] - Ammar, Saifullah; Mohamad Khairi,, Muhammad Irfan; Mohd Sayuti, Nor Fatin Najwa; Pauzi, Nur Samihah (2024)
Furniture Design is paramount for ensuring the comfort and well-being of individuals, especially within university environments. This furniture focusses on eco-friendly features, comfortable seating arrangements, sustainable design features, technology integration, functionality of a university campus and biophilic design. Incorporating elements such as parametric, traditional, fractal patterns, natural material and variety of colors. Additionally, the furniture design is inspired from centralized and repetition design principles. Every area of furniture has different of functions such as grouping meet, working area, disabled person, and biophilic design, can be used for community. By thoughtfully design furniture design, can be used for community that came to site location and university students to use the bench furniture.